2020
DOI: 10.31557/apjcp.2020.21.3.715
|View full text |Cite
|
Sign up to set email alerts
|

Muramyl Tripeptide Plus Chemotherapy Reduces Metastasis in Non-Metastatic Osteosarcoma: A Single-Center Experience

Abstract: Background: The immunomodulator mifamurtide plus a chemotherapy regimen has been shown to significantly improve the outcome in non-metastatic osteosarcoma patients. We report the results of the addition of mifamurtide to chemotherapy in newly diagnosed patients with osteosarcoma. Methods: A total of 36 children with osteosarcoma without detectable metastasis were treated between November 2010 and April 2018 at the Ankara University Department of Pediatric Oncology. Mifamurtide was added to the chemotherapy reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The trial examined the effects of MTP-PE with chemotherapeutic agents, finding that MTP-PE plus a four-drug chemotherapy regimen (doxorubicin, ifosfamide, cisplatin and methotrexate) showed the best event-free survival ( 81 ). Further studies have been done to complement observations from the INT-0133 trial ( 82 ). The use of this NOD2 agonist is approved for youth populations (2 to 30 years of age) as follow-up treatment after surgical removal of the main affected tissue ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The trial examined the effects of MTP-PE with chemotherapeutic agents, finding that MTP-PE plus a four-drug chemotherapy regimen (doxorubicin, ifosfamide, cisplatin and methotrexate) showed the best event-free survival ( 81 ). Further studies have been done to complement observations from the INT-0133 trial ( 82 ). The use of this NOD2 agonist is approved for youth populations (2 to 30 years of age) as follow-up treatment after surgical removal of the main affected tissue ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to another study from our country. Taçyıldız et al 22 reported that adding mifamurtide in the high-risk group decreased the probability of distant metastasis, increased the median time to distant metastasis, and improved event-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…26 MTP-PE was developed to help prevent lung metastasis in osteosarcoma. 27 Meyers et al and the Pediatric Oncology Group reported that the addition of this agent to the treatment had a positive effect on OS and EFS rates, but the results of the study are controversial due to the simultaneous addition of ifosfamide to the treatment. Moreover, the cost of MTP-PE is very high and beta-glucan is a cost effective and safe dietary supplement without serious side effects.…”
Section: Discussionmentioning
confidence: 99%